Serbian pork market analysis - Jeremić Marija (Ekonomika Poljoprivrede (1979), 2018)
Pig farming is the second most important branch of livestock production according to value of agricultural production, while pork meat is the most widely eaten meat in Serbia. As the one of the characteristics of pig market is cyclicality in the movement of production volumes and prices which can influence on the imbalance in supply and demand and in price fluctuations, the main aim of this paper was to analyse pork market in Serbia. Namely, in order to identify factors that influenced pork supply and demand, and to determine the presence of cyclical oscillations on pork market, pork market in Serbia was analyzed with supply and demand functions and with Cobweb model. The results indicated that factors which influenced on demand for pork were: personal consumption, retail price of pork and beef. On the other hand, on the supply side the most important factor was the price of pork. The results also indicated that in analyzed period in Serbia existed convergent type of Cobweb model.